Peran Citra Destinasi Pada Hubungan E-Wom Dengan Minat Kunjungan Wisatawan Di Pantai Losari, Kota Makassar - Sarapang, Vinny Corylitha; Surata, I Ketut; Utama, I Putu (Samarinda State Polytechnic, 2021)
This study sees and analyzes the direct effect of e-WOM on visit intention and destination image, the direct effect of destination image on visit intention, and the indirect effect of e-WOM on visit intention through destination image. The methods of this study used a quantitative approach. I collected data through online questionnaires with a total sample of 200 respondents. The sampling technique used is purposive accidental sampling. Data analysis used the SEM-PLS method. The results showed that e-WOM has no direct effect and an insignificant positive relationship on visit intention, e-WOM has a positive and significant direct effect on destination image, destination image has a positive and significant direct effect on visit intention, and e-WOM has a positive and significant indirect effect on visit intention through destination image or destination image became a mediator between e-WOM and visit intention.